Przedchorobowy iloraz inteligencji w schizofreniiCześć I: Przegląd metod do pomiaru przedchorobowego poziomu IQ - Stecka, Mariola; Karakuła-Juchnowicz, Hanna (Current Problems of Psychiatry, 2015)
Observations connected with the course of schizophrenia show the possibility of decline in the intellectual functioning during the disease process. Selection of proper methods to assess the level of IQ deterioration is extremely important in a reliable neuropsychiatric diagnosis and also the possibility of assessment of the rehabilitation programs effectiveness. Reliable diagnosis of the level of intellectu-al functioning of schizophrenic patient should not only consider current cognitive abilities but also the intellectual potential shown during the premorbid phase. The aim of this article was to analyze methods used in estimating the level of premorbid intelligence (PIQ). We described the following groups of methods used in the assessment of the premorbid IQ level: 1) the base methods connected with the demographic variables, 2) methods based on WAIS-R, 3) verbal methods, 4) combinations of those methods.